The Teachers' Perceptions of Religion-Based Gender Concepts in Early Childhood Education Institutions: The Gender-Responsive Education Implementation - Hanifah, Laili (Sekolah Tinggi Agama Islam Taruna Surabaya, 2025)
This study examines the understanding of gender concepts by early childhood education teachers with religious backgrounds from specific religious-based school environments in Yogyakarta. This study aims to investigate gender issues in education, especially in Early Childhood Education. This study generally aims to analyze the implementation of gender-responsive education in PAUD, while the specific objective is to describe the influence of teachers with certain religious backgrounds on the implementation and the influence of teachers' perceptions of gender concepts on the implementation. This study uses a quantitative cross-sectional survey method. The population in this study was all PAUD teachers in two sub-districts in Yogyakarta, totaling 52 PAUD teachers. A stratified cluster random sampling technique was conducted in two stages. Data was collected using closed questionnaires tested empirically for validity and reliability. The analysis techniques in this study were simple linear regression analysis and multiple linear regression, which had previously met the prerequisite tests for normality, linearity, heteroscedasticity, and multicollinearity. The results of the study indicate that: (1) There is an influence of the background of teachers who teach in religious-based schools on the learning carried out by these teachers in the classroom; (2) The teacher's perspective or perception has an influence on the implementation of gender-responsive education in the PAUD where the teacher works; (3) There is an influence of different religious backgrounds on the teacher's perception of gender concepts on the implementation of gender-responsive education in PAUD.